Characterization of the complete mitochondrial genome of Laomedia astacina De Haan, 1841 (Decapoda: Laomediidae) and its phylogenetic implications. Issue 3 (4th March 2022) - Guo, Dong; Zhang, Dandan; Tu, Zhong; Song, Lun; Dong, Jing; Wang, Weikuang
Abstract: In this study, we determined the complete mitochondrial genome (mitogenome) of Laomedia astacina De Haan, 1841 using next-generation sequencing technology. The total length of the mitogenome sequence of L. astacina is 14, 795 base pairs, including 13 protein-coding genes (PCGs), 22 transfer RNA genes, and two ribosomal RNA genes. The overall composition of the mitogenome is estimated to be 35.3% A, 38.0% T, 13.8% C, and 12.9% G, indicating that the L. astacina mitogenome is rich in A + T (73.3%). The phylogenetic relationships of 13 decapod species were constructed based on the 13 PCGs by the maximum-likelihood approach using IQtree software.